Piperacillin-tazobactam: prospects for use in real-world practice - Yu. M. Gomon (Реальная клиническая практика: данные и доказательства)
A review of the literature concerning the efficacy and safety of combined anti-pseudomonas protected ureidopenicillin piperacillin/tazobactam usage. Randomized clinical trials and their meta-analysis have demonstrated that piperacillin/ tazobactam among non-carbapenem β-lactams is an equally effective alternative to carbapenems in the treatment of severe infections, including those caused by extended-spectrum β-lactamase producing strains, regardless of the infection locus. It can be used in cases of carbapenem de-escalation if it is necessary. The use of this antimicrobial therapy strategy is justified not only from a clinical, but also from an economic point of view.